New species of Hemilissopsis Lane, 1959 (Coleoptera: Cerambycidae, Cerambycinae, Elaphidionini) - Hovore, Frank T.; Chemsak, John A. (Zootaxa, 2006)
A new species, Hemilissopsis fernandezae, in the elaphidionine genus Hemilissopsis Lane, is described from Costa Rica and Panama (Type locality, COSTA RICA: Limón Province, Sector Cerro Cocori).